ANALISIS PENGARUH CORPORATE SOCIAL RESPONSIBILITY, INTELLECTUAL CAPITAL, DAN KINERJA LINGKUNGAN TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2015)
This study examines the effect of corporate social responsibility and environmental performance of the company's financial performance. This research was conducted at the Indonesian Stock Exchange by using a go public manufacturing company as the unit of analysis. The sampling method used purposive sampling with the observation period from 2009 to 2013. Relationship and (or) influence between variable is described by using multiple regression analysis. The results showed that the corporate social responsibility and environmental performance has positive effect and significant to the company's financial performance. Whereas intellectual capital does not effect on the company's financial performance.Keywords: Corporate Social Responsibility, Intellectual Capital, Environmental Performance, and Financial Performance